International Handbook of Financial Literacy 2016
DOI: 10.1007/978-981-10-0360-8_15
|View full text |Cite
|
Sign up to set email alerts
|

Do the Financial Behaviours of College Students Vary by Their State’s Financial Education Policies?

Abstract: This study assesses the effectiveness of state mandates regarding high school financial education in the United States. Data (N = 12,967) were collected from current college students aged 18 and over via a web survey from 15 college campuses from various regions across the United States. A stratified random sampling method was employed. Overall, this study shows that the financial behaviours of college students vary by high school state mandates on financial education, even when controlling for students' chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
3
7
0
Order By: Relevance
“…This finding is supported by a study conducted by Gutter, Copur and Garrison (2010) in the University of Florida. They found that students from 7 states where a financial education course was compulsory had the highest financial knowledge.…”
Section: Discussion Ssupporting
confidence: 74%
See 1 more Smart Citation
“…This finding is supported by a study conducted by Gutter, Copur and Garrison (2010) in the University of Florida. They found that students from 7 states where a financial education course was compulsory had the highest financial knowledge.…”
Section: Discussion Ssupporting
confidence: 74%
“…The finding showed that students who did not take any finance course before were less knowledgeable than those who took a finance course previously. This finding is supported by a study conducted by Gutter, Copur and Garrison (2010) in the University of Florida. They found that students from 7 states where a financial education course was compulsory had the highest financial knowledge.…”
Section: Discussion Ssupporting
confidence: 74%
“…Importance of high school financial education proves also research at 15 universities in United States (Gutter et al, 2016). Financial behaviour of university students vary according to state mandates on financial education at high school.…”
Section: Financial Literacy Definition and Meaningmentioning
confidence: 93%
“…This relationship has been investigated outside of Turkey by several researchers (e.g. Kim, 2003; Gutter et al , 2016; Sohn et al , 2012). However, there are some tendencies regarding money ethics which are unique to the Turkish society.…”
mentioning
confidence: 99%